Analisis Teknik Percepatan Penjadwalan Konstruksi: Studi Kasus Simulasi Monte Carlo Puskesmas Pogalan di Jawa Timur, Indonesia - Achmad Yustofi; Wisnumurti Wisnumurti; Eko Andi Suryo (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
Lateness is a common risk factors in construction projects that may result in additional costs and fines according to the project agreement. In order to meet the predetermined specifications and completion schedule, the contractor must carefully plan the project and sequence the work tasks to create a rational schedule. This study focuses on the use of probabilistic scheduling to overcome delayed construction projects, especially in the case of the Pogalan Health Center development project. The process involves data collection, network planning, identification of critical paths, implementation of overtime hours, and Monte Carlo Simulation using @RISK software. The simulation results show that the probability of completion of the Pogalan Health Center construction project within 161 days is 95%-99%, the probability of completion within 154 days is 2.5%-20%, and the optimal duration is 160 days with a probability of 75% based on the random number distribution. highest. However, accelerating the completion of the project will incur additional costs. For example, completing it within 154 days will require an additional fee of Rp. 25.160.080,00. Keyword: construction, monte carlo simulation, probability, project, schedule